Phylogeography of post‐Pleistocene population expansion in a fungus‐gardening ant and its microbial mutualists - Alexander S. Mikheyev; Tanya Vo; Ulrich G. Mueller (Molecular Ecology, 2008)
Although historical biogeographical forces, such as climate‐driven range shifts, greatly influence the present‐day population genetic structure of animals and plants, the extent to which they affect microbial communities remains largely unknown. We examined the effect of postglacial expansion on the population structure of the northern fungus‐gardening ant Trachymyrmex septentrionalis and compared it with that of its two microbial mutualists: a community of lepiotaceous fungal cultivars and associated antibiotic‐producing Pseudonocardia bacteria. The ant population genetic structure showed signs of population expansion and subdivision into eastern and western phylogroups that likely originated in the Pleistocene — a pattern shared by many other North American taxa found in the same region. Although dispersal limitation was present in all three symbionts, as suggested by genetic isolation increasing with distance, the host's east–west subdivision of population genetic structure was absent from the microbial mutualist populations. While neither the cultivar nor the Pseudonocardia genetic structure was correlated with that of the ants, they were significantly correlated with each other. These results show that biogeographical forces may act differently on macro‐ and microscopic organisms, even in the extreme case where microbial mutualists are vertically transmitted from generation to generation and share the same joint ecological niche. It may be that historical climate change played a larger role in determining the population structure of the ant hosts, whereas present‐day environmental forces, such as pathogen pressure, determine the structure of associated microbial populations.